Classification of amyloidosis by model‐assisted mass spectrometry‐based proteomics - Palstrøm, Nicolai Bjødstrup (2022)
Funding Information: Funding: This research was partly funded by a “Center of Clinical Excellence” research grant from the Health Region of Southern Denmark to Odense Amyloidosis Center (AmyC). Publisher Copyright: © 2021 by the authors. Li-censee MDPI, Basel, Switzerland.